Ethical and legal considerations concerning the acceptance by doctors of "incentives" offered from pharmaceutical companies: a South African survey - Maholwana, Mandisa Joyce Gwendoline (My University, 2010)
Purpose There is limited literature available in South Africa concerning the interaction of doctors with the pharmaceutical industry. The purpose of this research report was to establish what South African doctors believe to be acceptable and appropriate incentives from the industry, highlight what they consider reasonable compensation for professional activities performed on behalf of the industry; and whether they perceive interaction with the industry’s marketing apparatus to be a significant influence on their prescribing habits. Methods A questionnaire was emailed to all active doctors in South Africa with email addresses from the Medpages® database. The survey was conducted in March 2009 - April 2009. The desired sample size was 500 General Practitioners (GPs) and Specialists in private practice. Results A final sample of 400 valid responses was analysed, representing 80% of desired sample. Majority of the respondents were male (74%) with an almost equal split between GPs (51.5%) and specialists (48.5%). The study revealed that 92% of the respondents accepted branding items whilst 60% of the respondents accepted personal gifts from the industry. The results revealed that 85% of the respondents felt that doctors should be paid for speaking at CMEs, and just over v half the sample (52%) felt they wanted to be paid their own rate as opposed to the industry rate. The investigation revealed that 77% of the respondents felt that their interaction with the industry influenced their prescribing habits and suggesting that such influence to be more pervasive with their colleagues, specifically 95% felt their colleagues are influenced by their interaction with industry (p< 0.001). About three quarters of the respondents (73%) believe patient management may be compromised if doctors’ prescribing habits are influenced by their interaction with the industry. Most respondents (72.5%) were either not aware or did not know of any regulations or guidelines with regards to acceptance of gifts by doctors from the industry. Conclusion This study demonstrated that perverse incentives continued to be given to doctors, and doctors have not shown a distinct aversion to accepting these perverse incentives and gifts. These perverse interactions have been shown in existing literature and in this research report to influence prescribing habits. Doctors do not seem to operate within their guidelines and legal framework, as stipulated by the HPCSA, when accepting these potentially harmful perquisites. What legal and ethical considerations are the doctors employing when accepting ‘incentives’ from industry is the question; and what is the doctor’s role in protecting his/her patients? Ignorance of the guidelines, as the study indicates to be the case, does not justify involvement in perverse relationships. Doctors have professional and personal moral responsibilities to ensure they familiarise vi themselves with guidelines regulating their professional conduct and ultimately protect the patients.
MSc (Med), Bioethics and Health Law, Faculty of Health Sciences, University of the Witwatersrand
Keywords: ethics; incentives